(untitled) (American Journal of Islam and Society, 1989)
The history of Islam in part of what is known today as Nigeria dates to about the loth Century. Christianity dates to the late 18th Century. By the middle of the 19th Century, when Nigerian newspapers began to appear on the streets of Nigeria, both religions had won so many followers and extended to so many places in Nigeria that very few areas were untouched by their influence. The impact of both religions on their adherents not only determined their spiritual life, but influenced their social and political lives as well. It therefore became inevitable that both religions receive coverage from most of the newspapers of the time. How the newspapers as media of information and communication reported issues about the two religions is the theme of this paper. Rationale for the Study The purpose of this study is to highlight the context in which such early newspapers operated and the factors that dictated their performance. This is because it is assumed that when a society faces external threat to its territory, culture, and independence, all hands (the press inclusive) ought to be on deck to resist the threat with all might. Were newspapers used as verbal artillery and how did they present each religion? It is also assumed that in a multireligious society a true press should be objective and serve as a vanguard in the promotion of the interest of the people in general and not create or foster an atmosphere of religious conflict. The study also aims at finding out whether the papers promoted intellectual honesty and fostered the spirit of unity particularly when the society was faced with the encroachment of the British who posed a threat to their freedom, culture, economy ...